Russian Economic Report, No. 29, Spring 2013 : Recovery and Beyond - World Bank (Washington, DC, 2014)
Russia's economy grew 3.4 percent in 2012, down from 4.3 percent in 2011. The economy of Russia slowed in the second half of the year due to weak net exports, negative base effects, and destocking at the end of the year. More than four years after the global financial crisis hit, the world economy remains sluggish. Industrial production lost momentum throughout last year, exports expanded only at a moderate pace, and imports even declined for three month during autumn 2012. Growth declined mainly due to weaker performance of investment. Inventories were flat as the restocking cycle after the crisis came to an end, and fixed investment expanded only moderately as business remained cautious about future prospects. The weaker performance of the tradable sectors reflects sluggish global demand and the poor agricultural harvest but also low competitiveness in parts of the industry, as growth declined for all three subsectors. The capital account strengthened in 2012 as net capital outflows decreased. According to preliminary estimates, the capital account deficit amounted to US$40.9 billion or 2 percent of Gross Domestic Product (GDP) in 2012, compared to US$76.2 billion or 4 percent of GDP in 2011. The labor market remains tight. The unemployment rate declined across the country, and vacancy and replacement rates increased. The number of poor people in Russia reached a record low. In the first nine months of 2012, some 17.2 million of people were below the poverty line, three million less than a year ago and the lowest number in the last two decades. The weak external environment, high inflation, flat oil prices and sluggish domestic demand are set to postpone a pickup in growth towards the second half of 2013. Nevertheless, modest growth and lower inflation are projected to reduce poverty further.